Dimensions of the Threat to the Self Posed by Deep Brain Stimulation: Personal Identity, Authenticity, and Autonomy (Diametros, 2021)
Deep Brain Stimulation (DBS) is an invasive therapeutic method involving the implantation of electrodes and the electrical stimulation of specific areas of the brain to modulate their activity. DBS brings therapeutic benefits, but can also have adverse side effects. Recently, neuroethicists have recognized that DBS poses a threat to the very fabric of human existence, namely, to the selves of patients. This article provides a review of the neuroethical literature examining this issue, and identifies the crucial dimensions related to the self which DBS may endanger—personal identity, authenticity, and autonomy. The most influential theories accounting for these dimensions are analyzed herein, and it is argued that most of these theories require further refinement. This paper also demonstrates the interrelation between personal identity, authenticity, and autonomy, and concludes that one can only fully understand the impact of DBS on the self when all of these factors are taken into account.
Keywords: self; personal identity; authenticity; autonomy; deep brain stimulation (DBS); neuroethics